Globalization, Tax Competition and the Future of Tax Systems - Tanzi, Vito. (Washington, D.C. : International Monetary Fund, 1996)
This paper discusses the implications for tax systems of globalization of capital markets and of economies. It shows the extent to which particular taxes are affected by the globalization process. It speculates on future developments in this area and on tax competition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet